2022
DOI: 10.1021/acsinfecdis.2c00121
|View full text |Cite
|
Sign up to set email alerts
|

Restoring and Enhancing the Potency of Existing Antibiotics against Drug-Resistant Gram-Negative Bacteria through the Development of Potent Small-Molecule Adjuvants

Abstract: The rapid and persistent emergence of drug-resistant bacteria poses a looming public health crisis. The possible task of developing new sets of antibiotics to replenish the existing ones is daunting to say the least. Searching for adjuvants that restore or even enhance the potency of existing antibiotics against drug-resistant strains of bacteria represents a practical and cost-effective approach. Herein, we describe the discovery of potent adjuvants that extend the antimicrobial spectrum of existing antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 113 publications
(179 reference statements)
0
12
0
Order By: Relevance
“…Additionally, we also noted that the PB-FL shows differences in degree of binding to polymyxin B-resistant versus susceptible strains (Figure S3C). Our results show that IITR00693 can potentiate the attachment of polymyxin B on the cell envelope of S. aureus (Figure B) and that the nature of the interaction of polymyxin B on the S. aureus cell envelope is quite strong, as we observed fluorescence signal after three washing steps.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we also noted that the PB-FL shows differences in degree of binding to polymyxin B-resistant versus susceptible strains (Figure S3C). Our results show that IITR00693 can potentiate the attachment of polymyxin B on the cell envelope of S. aureus (Figure B) and that the nature of the interaction of polymyxin B on the S. aureus cell envelope is quite strong, as we observed fluorescence signal after three washing steps.…”
Section: Resultsmentioning
confidence: 99%
“…Poly‐nitrogenous compounds, [5] cationic diamidine compounds, [16] and diimidazole compounds [14,15] that are not antibiotics on their own have been found to act as adjuvants that can sensitize Gram‐negative bacteria to a variety of antibiotics, which increases antibiotic activity. Specifically, we recently developed a series of pentamidine derived poly‐nitrogenous compounds that can readily accumulate in and weakly potentiate erythromycin against biofilm‐forming PA stain PA 9027 [5] .…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we recently developed a series of pentamidine derived poly‐nitrogenous compounds that can readily accumulate in and weakly potentiate erythromycin against biofilm‐forming PA stain PA 9027 [5] . Wang and co‐workers found that polyaromatic diamidine compounds can interact with the negatively charged outer membrane of Gram‐negative bacteria such as EC, AB, and KP, which increases antibiotic activity of novobiocin, rifampicin, and clarithromycin against these strains [16] . Recently, Melander and co‐workers found that 2‐aminoimidazole dimers can potentiate clarithromycin and related macrolide antibiotics against AB with low cytotoxicity against human cells through a mechanism unrelated to outer membrane perturbation.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decades, a series of such adjuvants have been elegantly developed for antibacterial sensitization and/or drug resistance reversion. [11][12][13][14][15][16][17][18][19][20] In addition to the genotypic resistance, the bacteria can become refractory to antibiotics without genetic mutations by transiently entering dormancy, which is known as phenotypic resistance or tolerance. 21 The subpopulation of bacteria with such a phenotypic resistance is termed as persisters, which reside mainly inside the biofilm, making them inaccessible to antibiotics and thus hard to be eradicated.…”
Section: Introductionsmentioning
confidence: 99%